Development of the School Counselor Efficacy for College Knowledge Questionnaire. (October 2021) - Nice, Matthew L.; Joseph, Matthew; Kolbert, Jered B.; Hilts, Derron N.; Crothers, Laura M.; Kratsa, Kristi
The present work describes the development of a new measure of school counselors' perceived self-efficacy regarding their knowledge of information and processes necessary to effectively guide their students through the college transition process. Researchers developed the School Counselor Efficacy for College Knowledge Questionnaire and examined data from a national sample of 600 school counselors to determine its psychometric properties and factor structure. Exploratory and confirmatory factor analyses supported use of a modified five-factor model. Results showed strong internal consistency and preliminary evidence for convergent and divergent validity of the resultant scales.